Sternal Dehiscence Accompanied by Protrusion of the Left Lung Through the Chest Wall - Celik, Sezai; Gurer, Onur; Aydemir, Cuneyt (The Thoracic and Cardiovascular Surgeon, 2013)
We report an almost complete protrusion of the lung through the anterior chest wall occurring as a complication following sternal dehiscence. Emergency treatment is mandatory since it has a high potential for incarceration, hemopneumothorax, respiratory failure, and infection. Twenty-eight days after coronary by-pass surgery, the left lung of a 66-year-old male patient almost completely protruded through the sternotomy incision in the chest wall; the lung tissue was successfully reduced and the sternotomy was closed. Recurrence was not observed within the 6-month follow-up period, his general condition was good. The clinical course of the patient was retrospectively reviewed, and this case was reported with a unique complication.
Keywords: sternum; wound dehiscence; pleura; lung